2017
DOI: 10.1038/s41598-017-09329-4
|View full text |Cite
|
Sign up to set email alerts
|

Potential Use of MALDI-ToF Mass Spectrometry for Rapid Detection of Antifungal Resistance in the Human Pathogen Candida glabrata

Abstract: The echinocandins are relatively new antifungal drugs that represent, together with the older azoles, the recommended and/or preferred agents to treat candidaemia and other forms of invasive candidiasis in human patients. If “time is of the essence” to reduce the mortality for these infections, the administration of appropriate antifungal therapy could be accelerated by the timely reporting of laboratory test results. In this study, we attempted to validate a MALDI-ToF mass spectrometry-based assay for the ant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
54
0
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(58 citation statements)
references
References 26 publications
2
54
0
2
Order By: Relevance
“…So far, rapid susceptibility testing by MALDI-TOF MS has mainly been described for bacteria (23,27,(30)(31)(32)(33). One research group has reported on a rapid AFST approach by analyzing the similarities of the MALDI-TOF MS profile spectra derived from different setups containing increasing antibiotic concentrations (34)(35)(36). MBT ASTRA is a semiquantitative method that was first applied for the detection of meropenem susceptibility in bacteria derived from culture plates or from positive blood cultures within 1 to 4 h (32).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, rapid susceptibility testing by MALDI-TOF MS has mainly been described for bacteria (23,27,(30)(31)(32)(33). One research group has reported on a rapid AFST approach by analyzing the similarities of the MALDI-TOF MS profile spectra derived from different setups containing increasing antibiotic concentrations (34)(35)(36). MBT ASTRA is a semiquantitative method that was first applied for the detection of meropenem susceptibility in bacteria derived from culture plates or from positive blood cultures within 1 to 4 h (32).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, the approach of Vella and colleagues (34) analyzed changes in the MS profile spectra induced by antifungals. A recent study of the same group (36) has shown that this approach does not accurately work for C. glabrata strains that are resistant to anidulafungin and that have known FKS2 mutations (36). The complete assay setup of MBT ASTRA is like that of the commonly accepted microdilution method, which is generally accepted as the gold standard.…”
Section: Discussionmentioning
confidence: 99%
“…In another study, an AFST-based MALDI-TOF assay was developed to detect C. glabrata isolates resistant to anidulafungin within 3 h. This method was based on the detection of changes in the protein profile spectrum relative to the antifungal concentration by MALDI-TOF MS. The AFST-based MALDI-TOF assay was useful to detect strains with mutations in FKS1; however, it failed to detect C. glabrata resistant isolates carrying known FKS2 mutations (27).…”
Section: Discussionmentioning
confidence: 99%
“…Matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry has been successfully exploited for species‐level fungal pathogen identification based on unique proteomic signatures . This approach has been particularly useful in the identification of rare and commonly misidentified fungal species, including unusual Aspergillus pathogens, and the identification of antifungal drug‐resistant Candida strains . Moreover, quantitative bottom‐up proteomic analysis combined with selected reaction monitoring has discovered secreted cryptococcal proteins in infected tissue samples, suggesting the utility of such techniques for detection of diagnostic biomarkers of fungal infection .…”
Section: Future Prospects For Emerging Fungal Disease: Diagnosis and mentioning
confidence: 99%
“…210,211 This approach has been particularly useful in the identification of rare and commonly misidentified fungal species, including unusual Aspergillus pathogens, 212,213 and the identification of antifungal drug-resistant Candida strains. 214,215 Moreover, quantitative bottom-up proteomic analysis combined with selected reaction monitoring has discovered secreted cryptococcal proteins in infected tissue samples, suggesting the utility of such techniques for detection of diagnostic biomarkers of fungal infection. 216 Finally, compelling recent work has exploited engineered Saccharomyces cerevisiae as a biosensor capable of detecting fungal pathogen-derived peptides in order to develop a low-cost and nontechnical fungal diagnostic.…”
Section: Future Prospects For Emerging Fungal Disease: Diagnosis and mentioning
confidence: 99%